2018
DOI: 10.1161/jaha.118.010317
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Associated With the Risk of Incident Venous Thromboembolism: A Metabolomic Analysis

Abstract: Background Venous thromboembolism ( VTE ) is a complex thrombotic disorder that constitutes a major source of mortality and morbidity. To improve understanding of the cause of VTE , we conducted a metabolomic analysis in a case‐control study including 240 incident VTE cases and 6963 controls nested within 3 large prospective population‐based cohorts, the Nurses’ Health Study, the Nurses’ Health Study II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…Given that application of metabolomics technology to epidemiological studies is an emerging field, we conducted a survey of participating COMETS cohort representatives to gain insights into the strategies and procedures used for analyzing metabolomics data, including data pre-processing, analysis, and reporting of results. With a range of experience levels analyzing metabolomics data, participating COMETS cohorts have analyzed and published on both targeted and untargeted metabolomics data from a variety of study designs in relation to disease risk factors [8,18,19,20,21,22,23,24,25,26,27] and many disease outcomes, predominantly cancer, CVD, and diabetes [28,29,30,31,32,33,34,35,36,37,38,39,40]. However, there was little consensus on approaches to data pre-processing, statistical analysis or reporting of results, which is echoed in the broader metabolomics community [13].…”
Section: Discussionmentioning
confidence: 99%
“…Given that application of metabolomics technology to epidemiological studies is an emerging field, we conducted a survey of participating COMETS cohort representatives to gain insights into the strategies and procedures used for analyzing metabolomics data, including data pre-processing, analysis, and reporting of results. With a range of experience levels analyzing metabolomics data, participating COMETS cohorts have analyzed and published on both targeted and untargeted metabolomics data from a variety of study designs in relation to disease risk factors [8,18,19,20,21,22,23,24,25,26,27] and many disease outcomes, predominantly cancer, CVD, and diabetes [28,29,30,31,32,33,34,35,36,37,38,39,40]. However, there was little consensus on approaches to data pre-processing, statistical analysis or reporting of results, which is echoed in the broader metabolomics community [13].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly diminished levels of many long-chain ACs in VTE patients (values below the 20th percentile of controls) could suggest that some patients had the deficiency of plasma anticoagulant lipids resulting from a shortage of multiple long-chain ACs. Similarly, Jiang et al [ 1 ] who studied 240 incident VTE cases (including 125 incident PE cases) and 6963 controls revealed that C5 carnitine was significantly associated with incident VTE. They demonstrated that diacylglycerols were increased in both VTE and PE patients, but their exact role in the pathomechanism of VTE is unknown.…”
Section: Deep Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 91%
“…The study of metabolites can reveal the physiologic state before disease onset as well as the complex interplay between genes, environmental risk factors, and VTE [ 1 ]. This technique has been used in the study of cardiovascular disease risk, however, there are just a few publications concerning metabolic profiling in VTE.…”
Section: Metabolomics and Related Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovering these alterations in the plasma and platelet lipidome in arterial thrombosis has further highlighted the importance of lipids in thrombosis, and it is hoped that novel approaches may also show promise in the prediction of venous thrombosis. In this regard, recent studies suggest that several lipid and metabolites pathways are altered in acute VTE [149][150][151]. Deguchi et al have demonstrated an association between low plasma acylcarnitine levels and venous thrombosis and determined that acylcarnitines have anticoagulant activity by way of their ability to bind to, and inhibit, factor Xa, establishing a potential factor in the pathogenesis of venous thrombosis [144].…”
Section: Metabolomics and Lipidomics In Vtementioning
confidence: 99%